Behavior of the Bispectral Index (BIS) and Electromyography (EMG) in Bitches Undergoing Ovariohysterectomy - Santos, Ivan Felismino Charas dos; Bino Correa, Denise; Dirceu Pazdiora, Raul; Vinicius dos Santos Rosa, Vinicius; Cunico Machado, Jonas; Amara Garcia Alves, Liandra; Jane Evangelista Moura, Sarha; Mansur Muniz, Igor; Rabelo Andrade, Evelyn; do Carmo Silva, Fernando (Acta Scientiae Veterinariae, 2025)
Background: The bispectral index (BIS) is a method used to monitor patients during surgical procedures. However, studies on the use of BIS in bitches anesthetized with different protocols and undergoing ovariohysterectomy are scarce in the literature. This study aimed to assess the behavior of BIS and electromyography (EMG) in bitches anesthetized with ketamine and midazolam in combination with xylazine, medetomidine, or dexmedetomidine. Materials, Methods & Results: Thirty bitches anesthetized with ketamine and midazolam were divided into 3 groups of 10 animals each: dexmedetomidine (20 µg/kg/h), medetomidine (30 µg/kg/h), and xylazine (1000 µg/kg/h). All animals underwent an 8-h fasting period for food and a 2-h water restriction before surgery. A trichotomy was performed in the frontal and temporal regions to allow for the placement of BIS monitor sensors, as well as on the thoracic limbs for venous catheter insertion. The animals were maintained under spontaneous ventilation, receiving an inspired oxygen fraction of 100% at a continuous gas flow rate of 20 mL/kg/min. Vital parameters were monitored using a multiparameter monitor. BIS and EMG values were recorded using a BIS monitor at the following time points: before pre-anesthetic medication (control), 15 min after pre-anesthetic medication, 10 min after anesthetic induction and orotracheal intubation, at the end of the ovariohysterectomy, and 30 min after the beginning of the surgical procedure. Postoperatively, all animals received meloxicam (0.2 mg/kg) subcutaneously for analgesia. Upon regaining quadrupedal posture, they were discharged to their owners with prescriptions for meloxicam (0.2 mg/kg) every 24 h for 3 days and dipyrone (20 mg/kg) every 8 h for 5 days, both administered orally. A one-way analysis of variance (ANOVA) was performed to compare the means of each variable at different time points, followed by a post-hoc Tukey test. A significance level of 5% was adopted. A significant reduction in BIS was observed after pre-anesthetic medication only in the dexmedetomidine group (P < 0.05). After anesthetic induction, BIS values progressively decreased in all groups, with the dexmedetomidine group showing significantly lower values compared to the medetomidine and xylazine groups. EMG values significantly decreased in all groups throughout the study period. Discussion: The study’s hypothesis was partially confirmed, as only the dexmedetomidine group showed significantly lower BIS and EMG values compared to the other groups at 15 min after pre-anesthetic medication and 10 min after anesthetic induction and orotracheal intubation. The lower BIS and EMG values observed in the dexmedetomidine group at 15 min after pre-anesthetic medication and 10 min after anesthetic induction and orotracheal intubation align with findings from previous studies using dexmedetomidine via continuous infusion or epidural administration. However, this reduction contradicts findings from other studies suggesting that BIS is not applicable in patients receiving ketamine. Studies have shown that dogs treated with medetomidine/isoflurane exhibit a marked BIS reduction compared to those receiving isoflurane alone. Similarly, in rats, EMG values significantly decreased following drug infusion. However, the results of this study suggest a disproportionate reduction between BIS and EMG values. Dexmedetomidine provided adequate anesthesia for ovariohysterectomy, as evidenced by the significant reductions in BIS and EMG values. Keywords: alpha-2 agonist, dogs, continuous infusion, TIVA.